Optimalisasi Prinsip Ekonomi Syariah dalam Meningkatkan Kinerja Usaha Fotokopi dan ATK Rijan Pacet - Sudira, Didi (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2023)
This study explores the optimization of Islamic economic principles in enhancing the performance of a photocopy and stationery business, Rijan Pacet, located within the Riyadlul Jannah boarding school environment. Utilizing a qualitative approach through in-depth interviews, participatory observation, and document analysis, the research aims to understand how the application of Sharia principles can contribute not only to the financial performance of the business but also to social and environmental welfare. The findings suggest that the integration of fairness, transparency, and mutual welfare principles into business operations significantly benefits all stakeholders involved. Collaboration with educational institutions within the boarding school, leveraging information technology, and implementing Sharia-based marketing strategies are identified as key factors in expanding market reach and raising public awareness of Islamic economics. The study concludes that the photocopy and stationery business has a broad opportunity to grow and contribute to the development of Islamic economics in Indonesia by applying Sharia principles in its operations.